Perbandingan Hukum Mengenai Pagar Pembatas Bandar Udara Menurut Hukum Penerbangan Internasional dan Nasional - Prasetia, Addin; Novianti, Novianti; Ardianto, Budi (Faculty of Law, Universitas Jambi, 2022)
Aviation is one method of transportation that is quite widely used by humans in carrying out activities related to the movement of people and goods. This article discusses the comparison of the suitability of legal aspects regarding guardrails at airports in Law Number 1 of 2009 concerning Aviation as the legal basis for aviation in Indonesia with Annex XIV Aerodromes International Civil Aviation Organization as a technical rule of Article 37 Convention on International Civil Aviation. Aviation 1944 as an international legal standard regarding airport security as part of the aviation element in the world. The research method used is a normative juridical research type. The results showed that there was a discrepancy between the provisions regarding airport guardrails in Law Number 1 of 2009 concerning Aviation as a national legal product and Annex XIV: Aerodromes International Civil Aviation Organization as an international legal product. Aviation is one method of transportation that is quite widely used by humans in carrying out activities related to the movement of people and goods. This article discusses the comparison of the suitability of legal aspects regarding guardrails at airports in Law Number 1 of 2009 concerning Aviation as the legal basis for aviation in Indonesia with Annex XIV Aerodromes International Civil Aviation Organization as a technical rule of Article 37 Convention on International Civil Aviation. Aviation 1944 as an international legal standard regarding airport security as part of the aviation element in the world. The research method used is a normative juridical research type. The results showed that there was a discrepancy between the provisions regarding airport guardrails in Law Number 1 of 2009 concerning Aviation as a national legal product and Annex XIV: Aerodromes International Civil Aviation Organization as an international legal product.